The SARS-CoV-2 RNA polymerase is a viral RNA capping enzyme - Walker, AP; Fan, H; Keown, JR; Knight, ML; Grimes, JM; Fodor, E (Oxford University Press, 2021)
SARS-CoV-2 is a positive-sense RNA virus responsible for the Coronavirus Disease 2019 (COVID-19) pandemic, which continues to cause significant morbidity, mortality and economic strain. SARS-CoV-2 can cause severe respiratory disease and death in humans, highlighting the need for effective antiviral therapies. The RNA synthesis machinery of SARS-CoV-2 is an ideal drug target and consists of non-structural protein 12 (nsp12), which is directly responsible for RNA synthesis, and numerous co-factors involved in RNA proofreading and 5′ capping of viral RNAs. The formation of the 5′ 7-methylguanosine (m7G) cap structure is known to require a guanylyltransferase (GTase) as well as a 5′ triphosphatase and methyltransferases; however, the mechanism of SARS-CoV-2 RNA capping remains poorly understood. Here we find that SARS-CoV-2 nsp12 is involved in viral RNA capping as a GTase, carrying out the addition of a GTP nucleotide to the 5′ end of viral RNA via a 5′ to 5′ triphosphate linkage. We further show that the nsp12 NiRAN (nidovirus RdRp-associated nucleotidyltransferase) domain performs this reaction, and can be inhibited by remdesivir triphosphate, the active form of the antiviral drug remdesivir. These findings improve understanding of coronavirus RNA synthesis and highlight a new target for novel or repurposed antiviral drugs against SARS-CoV-2.